Classroom behaviour management to support children's social, emotional, and behavioural development - Nye, E (2017)
Introduction: Children's social, emotional, and behavioural difficulties are associated with reduced academic performance, stressed teacher-child relationships, and other negative academic and life outcomes. The Incredible Years Teacher Classroom Management (IY TCM) programme is one intervention developed to address problematic behaviours via training teachers to use positive and proactive management strategies. The overall aim of this DPhil is to use the Incredible Years Teacher Classroom Management programme as a case study for applying mixed methods at the systematic review level to ascertain what is known about both the programme's effectiveness and how people experience the course, and subsequently to use the systematic review's findings as a springboard (rather than as an end goal) for more exploratory research into 'for whom' the programme might work. Method: Study One is a mixed methods systematic review of IY TCM. It applied multilevel meta-analysis to RCT outcome data and grounded theory meta-synthesis to interview and focus group data on stakeholders' experiences of IY TCM. Quantitative and qualitative findings were cross-synthesised and mapped using an integrative grid. Study Two moves the field forward by filling a gap in the evidence base, as identified in Study One. Semi-structured telephone interviews were conducted with special educational needs coordinators (SENCos) across Devon, exploring the acceptability and appropriateness of expanding IY TCM to the subgroup of children with special educational needs (SEN) in mainstream schools. Data were analysed thematically and mapped onto IY TCM content. Results: In Study One, nine studies reported across 14 papers met inclusion criteria for either quantitative or qualitative strands of this systematic review. Multilevel meta-analysis of RCTs (n=4) indicated that the programme produced teacher- and child-level results in the desired directions. Clear trends across all measured outcomes favoured the intervention group over the treatment-as-usual comparison. Qualitative meta-synthesis (n=5) illuminated a cyclical learning process and broader conceptualisation of teacher and child outcomes than was evident in the quantitative evidence. Notably, RCT data on teacher outcomes were limited to self-reported or observed behaviours, while teachers described other benefits from IY TCM including increased knowledge and emotional well-being. Cross-synthesis of findings from the two review strands highlighted harmony across the RCT and qualitative evidence but also a number of areas in which constructs that were prioritised by one type of research were not integrated into the other. Study Two generated classroom management strategies from SENCos, which aligned closely with strategies taught in IY TCM, indicating that IY TCM would be both acceptable and applicable (if not sufficient) for use when working with children identified with SEN and behavioural difficulties in schools. Discussion: Based on the positive effects of implementing IY TCM despite very few studies to power analyses, the programme appears to offer tangible benefits to both teachers and children. It is possible that results are underestimated due to limited types of outcomes measured and absence of experiential data from additional stakeholders (e.g., parents). Depending on current provision of special educational needs services, schools operating inclusion models are likely to find these strategies beneficial for children identified with SEN, and this subgroup should be explicitly examined in future IY TCM studies.